PERBEDAAN PENDEKATAN KONTEKSTUAL BERBANTUAN ALAT PERAGA DENGAN PENDEKATAN SCIENTIFIC TERHADAP KETERAMPILAN BERPIKIR KREATIF - Sulitrayanti, Ni Komang; Saehana, Sahrul; Jarnawi, Muhammad (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This research was conducted to look at the differences between the contextual approach assisted by teaching aids and the scientific approach to creative thinking skills. This type of research is a quasi-experimental design with a non-equivalent control group design. The population of this study was all students of class X SMA Negeri 5 Palu. The sampling technique used in this study was purposive sampling with the research sample being class X MIPA 5 as the experimental group 1 and class X MIPA 6 as the experimental group 2. The instrument for students' creative thinking skills was in the form of an essay test that had been validated through construction validity. The test of students' creative thinking skills obtained showed that the average score of the experimental group was 50.65%. Where this result is lower than the control group, which is 52.79%. Hypothesis test T-test (two parties), obtained t_count = -1.21 and t_0.975 = 2.02 at the level of significance = 0.05. This means that the value of t_count is in the reception area of ​​H_0. It is concluded that there is no difference between the contextual approach assisted by teaching aids and the scientific approach to creative thinking skills